Comparison Of The Economic Thought Of Ibn Khaldun, Abu Hamid Al-Ghazali, And Ibn Taimiyyah Related To Prices And Market Mechanisms - Nurhikmah; Siradjuddin; Suci Septiani (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to compare the economic thinking of three great Islamic scholars, namely Ibn Khaldun, Abu Hamid Al-Gazali, and Ibn Taymiyyah, specifically regarding the concept of price and market mechanisms. Ibn Khaldun emphasized the importance of the forces of supply and demand in determining prices and viewed prices as a reflection of socio-economic dynamics. Al-Gazali emphasized the ethical and moral dimensions of trade, emphasizing the prohibition of hoarding and the importance of justice so that market mechanisms do not harm society. Meanwhile, Ibn Taymiyyah emphasized that prices are basically formed naturally through market interactions, but the state has the right to intervene if fraud and injustice disrupt the balance. A comparison of these three figures shows a similar view regarding the role of the market as the main mechanism and price formation, but differs in the emphasis on social, ethical, and regulatory aspects. Classical Islamic economic thought has provided a relevant normative and practical foundation for understanding modern market mechanisms in a just manner